A morte veio visitar meu avô e esqueceu quem ela era - Pereira, Moema Vilela (2013)
The present dissertation is produced in a relatively new and still-expanding area in Brazil Creative Writing, which culminates in the submission and oral defense of a creative work (in this case, a novel). It presents also, briefly, the creative process. The novel A morte veio visitar meu avô e esqueceu quem ela era seeks to plunge into the different worldviews of the five main characters, whose lives intersect during the final days of Bepe Coppini. The characters are Bepe Coppini himself, grandson Leonardo and his girlfriend Graviska, sister-in-law Catarina and son Santiago. Built upon the organicity of the construction of the protagonists, the novel evokes various moments in time and space, such as the Italian immigration in Southern Brazil, the military dictatorship of 1964 and the globalised, fleeting, technological and critical contemporary world. Including experiments on narrative focus and a story of love and infidelity in the foreground, the novel relies on protagonists of different ages, geographical origins, social classes, life stories, religious beliefs and favorite authors, hence offering complex and divergent views about the misadventures of the human heart in search of happiness and love